2016
DOI: 10.1093/femspd/ftw062
|View full text |Cite
|
Sign up to set email alerts
|

Protein-based profiling of the immune response to uropathogenicEscherichia coliin adult patients immediately following hospital admission for acute cystitis

Abstract: Urinary tract infections (UTIs) caused by uropathogenic Escherichia coli (UPEC) are common infections in humans. Despite the substantial healthcare cost represented by these infections, the human immune response associated with the infection immediately following the onset of symptoms in patients remains largely undefined. We performed a prospective study aimed at defining the milieu of urinary cytokines in adult inpatients in the 24-48 h period immediately following hospital admission for acute cystitis due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…It was of particular interest that microbial colonisation and significant urinary E. coli loads in the ASB / rUTI susceptible cohort (> 10 5 CFU/ml), were marked by the synthesis of the immunomodulatory cytokine IL-10 [42, 43]. Observations in humans and IL-10 deficient mice, support a key role for IL-10 in defending the urinary tract from UPEC infection [43, 44]. Moreover recent studies exploring UT microbial colonisation in older female mice have specifically identified IL-10 as a significant factor in their susceptibility to colonisation by E. coli [37].…”
Section: Discussionmentioning
confidence: 99%
“…It was of particular interest that microbial colonisation and significant urinary E. coli loads in the ASB / rUTI susceptible cohort (> 10 5 CFU/ml), were marked by the synthesis of the immunomodulatory cytokine IL-10 [42, 43]. Observations in humans and IL-10 deficient mice, support a key role for IL-10 in defending the urinary tract from UPEC infection [43, 44]. Moreover recent studies exploring UT microbial colonisation in older female mice have specifically identified IL-10 as a significant factor in their susceptibility to colonisation by E. coli [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although, to our knowledge, our observations regarding the direct effects of IL-4 on the urothelium are the first to directly link type-2 immune responses to urogenital schistosomiasis and bladder pathogenesis, they may have relevance beyond S. haematobium infection. For instance, IL-4 may be important in other bladder-specific conditions, namely, acute cystitis and overactive bladder (59,60). Future work focusing on urothelial IL-4 receptor signaling in various diseases may reveal novel diagnostic and therapeutic approaches and will promote our understanding of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to focus on proinflammatory cytokines due to their primary induction by UPEC and because they have been linked to the progression of the infection (Davidoff et al, 1997; Godaly et al, 1997; Jones-Carson et al, 1999; Khalil et al, 2000; Hertting et al, 2003; Spencer et al, 2014; Ambite et al, 2016; Sundac et al, 2016). The concentration range investigated was 0.5–40 ng/ml, as these cytokines are found in the urine in a concentration range of 0.5–10 ng/ml, however, urine is very diluted (Sundac et al, 2016). The concentration that an adhered bacteria (to epithelial cells) can be exposed to can be much higher in the micro-milieu, hence the choice of higher concentrations also.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, IL-1β, IL-6, IL-8 and IFN-γ are some of the major cytokines being released during UTI (Spencer et al, 2014). Levels of up to 800 (TNF-α), 7000 (IL-1β), 1500 (IL-6), 8000 (IL-8) and 1400 pg/ml (IFN-γ) have been found in the urine of patients with acute cystitis (Sundac et al, 2016). IL-1β is expressed by bladder epithelial cells (Nagamatsu et al, 2015; Demirel et al, 2018) and has been shown to be important for clearance of UPEC (Hertting et al, 2003; Ambite et al, 2016).…”
Section: Introductionmentioning
confidence: 99%